2013
DOI: 10.1128/aac.01465-12
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Analysis of Albendazole Sulfoxide Enantiomers Shows that (+)-( R )-Albendazole Sulfoxide Is the Active Enantiomer against Taenia solium

Abstract: Albendazole is an anthelmintic drug widely used in the treatment of neurocysticercosis (NCC), an infection of the brain with Taenia N eurocysticercosis (NCC) is a major cause of adult-onset seizures and epilepsy in many areas of the developing world. It is an infection with the larval cyst form of the cestode tapeworm Taenia solium acquired through the accidental ingestion of ova shed in the feces of human tapeworm carriers. The released oncospheres find their way to the bloodstream and are carried throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Furthermore, Paredes et al demonstrated that ( R )-albendazole sulfoxide had greater anthelmintic activity against T . solium when compared to ( S )-albendazole [ 45 ]. Our data, along with these and other parasitic studies [ 46 ], provides clear evidence that compound chirality represents an important consideration for drug discovery progression and putative target identification.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Paredes et al demonstrated that ( R )-albendazole sulfoxide had greater anthelmintic activity against T . solium when compared to ( S )-albendazole [ 45 ]. Our data, along with these and other parasitic studies [ 46 ], provides clear evidence that compound chirality represents an important consideration for drug discovery progression and putative target identification.…”
Section: Discussionmentioning
confidence: 99%
“…Albendazole is an anthelmintic drug widely used in the treatment of neurocysticercosis, an infection of the brain with Taenia solium cysts. Use of (+)-(R)-Albendazole sulfoxide ( Figure 12) enantiomer alone may lead to increased efficacy and/or less toxicity compared to albendazole [59]. Mephedrone (Figure 13) most probably as a racemic mixture of the R and S enantiomers is a synthetic psychoactive substance.…”
Section: Representative Chiral Drugsmentioning
confidence: 99%
“…After absorption, albendazole is subject to rapid and extensive first‐pass metabolism into the chiral metabolite, albendazole sulfoxide, which is the entity responsible for its cysticidal activity . The (+)‐ enantiomer of albendazole sulfoxide has the greatest pharmacologic activity against T. solium . Albendazole is subject to high intrinsic clearance which may be a result of poor absorption, extensive first pass metabolism, or a combination of these factors.…”
Section: Pharmacokinetics Of Albendazolementioning
confidence: 99%
“…10 The (þ)-enantiomer of albendazole sulfoxide has the greatest pharmacologic activity against T. solium. 11 Albendazole is subject to high intrinsic clearance 12 which may be a result of poor absorption, extensive first pass metabolism, or a combination of these factors. Albendazole sulfoxide also exhibits plasma protein binding (62-72%).…”
Section: Pharmacokinetics Of Albendazolementioning
confidence: 99%